Rehabilitating Eden: archetypal images of Malaya in travel writing - Ahmad, Siti Nuraishah; Pillai, Shanthini; Md. Yusof, Noraini (Berghahn Books Ltd., 2011)
This article links Jungian literary criticism on archetypes with contemporary postcolonial theories on colonial discourse in travel writing (David Spurr) and the worlding of a colonized land (Gayatri Spivak) in order to understand the pattern of images in European travel writing that created the fiction of Malaya. This fiction is created through a process of worlding by European travelers from the sixteenth century to the early twentieth century. The practice of Islam and magic among the Malays was represented as contributing to the degeneration of Malaya. The resulting image is that of an Eden that has fallen into ruin and that needs to be transformed back into paradise by the white man.